Essential oil yield and composition of native species of the Myrtaceae family from “Campos Gerais” of the Atlantic Forest in Parana State - Silva, Luiz Everson da; Amaral, Wanderlei do; Deschamps, Cícero; Biasi, Luiz Antonio; Bizzo, Humberto Ribeiro; Pinto, Marco Antonio Silva (Ciência e Natura, 2019)
This work aimed to evaluate the essential oil yield and composition of the species Myrciaria delicatula, Campomanesia xantocarpha, Campomanesia aurea, Calyptranthes clusiifolia, Myrcia splendens, Eugenia osoriana, Myrciaria tenella, Myrceugenia reitzii, Calyptranthes concinna e Myrcia arborensis from a segment of the Atlantic Forest of Parana State. The sample collections for essential oil extraction, photographic records and herbarium specimen’s preparation for botanical species identification were made at the Private Reserve of Natural Heritage (PRNP) Butuguara in Palmeira (PR), with “Campos Gerais” formations. Myrceugenia reitzii showed eesential oil yield superior to other species and the essential oil yield of all species increased after drying. The chemical composition in the samples showed mono and sesquiterpenes, being the sesquiterpenes in higher percentages. The drying conditions affected the essential oil composition of the for the majority of the evaluated species